CADASTRATION OF STRICT PROTECTION LANDS. INFORMATION INTERACTION OF CADASTERS - Петраковська, Ольга; Богатырь, Дария (SWorldJournal, 2021)
The article studies the current state of cadastre of lands of strict protection and information interaction of the State Land Cadastre with the State Cadastre of Territories and Objects of the Natural Reserve Fund. The main problems of filling the inform